EKSPLORASI FAKTOR-FAKTOR KEGAGALAN BADAN USAHA MILIK DESA - Taufik Raharjo; Aditya Wirawan; Ambang Aries Yudanto; Muhammad Setiawan Kusmulyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study is to explore the factors that have the potential to influence the failure of BUM Desa. Exploration of factors that have the potential to influence the failure of BUM Desa is based on a qualitative study by collecting data and information using interviews with key figures related to the management of BUM Desa. The results of this study indicate that the factors that have the potential to influence the failure of BUM Desa are as follows (1) Government Regulations Related to the Pandemic, (2) Adaptability of BUM Desa Business Models, (3) Unprofessional BUM Desa Governance, (4) Vision of BUMdes Not yet Visionary, (5) Low Community Participation, (6) Low Capacity and Skills of Human Resources in BUM Desa, (7) Leadership of Village Heads, (8) Mindset of Village Heads who are Not Agile, (9) Macroeconomic Conditions Not yet Stable, (10) Negative Externalities from Government Policies, and (11) Unfavorable Village Local Political Atmosphere.